2010
DOI: 10.1002/chin.201029197
|View full text |Cite
|
Sign up to set email alerts
|

ChemInform Abstract: Chemical Constituents Isolated from Andrographis paniculata

Abstract: Chemical Constituents Isolated from Andrographis paniculata -[isolation and structure determination of six diterpenoides of type (I)/(II) and three diterpenoidal glycosides]. -(KULYAL*, P.; TIWARI, U. K.; SHUKLA, A.; GAUR, A. K.; Indian J.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0
2

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 0 publications
1
14
0
2
Order By: Relevance
“…The characteristic exocyclic methylene protons for AB-2 diterpenoids were observed at δ 4.595 (brs, 1H) and 4.455 (brs, 1H) in 1 HNMR as well as at δ 108.86 in 13 C, respectively. The 1 H-and 13 C-NMR (in CDCl 3 ) spectra of AB-2 suggested a diterpenoid compound with a structure similar to that of 14-deoxyandrographolide (Poonam et al, 2010) (Fig. 2).…”
Section: Resultsmentioning
confidence: 93%
See 1 more Smart Citation
“…The characteristic exocyclic methylene protons for AB-2 diterpenoids were observed at δ 4.595 (brs, 1H) and 4.455 (brs, 1H) in 1 HNMR as well as at δ 108.86 in 13 C, respectively. The 1 H-and 13 C-NMR (in CDCl 3 ) spectra of AB-2 suggested a diterpenoid compound with a structure similar to that of 14-deoxyandrographolide (Poonam et al, 2010) (Fig. 2).…”
Section: Resultsmentioning
confidence: 93%
“…IR (cm −1 ) ν: 3367, 1736, 1646, 896. 1 H NMR (600 MHz, in DMSO-d6), δ (ppm): 1.327 (m, 2H, C1-CH 2 ), 2.045 (brs, 1H, C2-CH 2 ), 1.999 (o, 1H, C2-CH 2 ), 3.353 (o, 1H, C3-CH-), 1.463 (o, 1H, C5-CH-), 2.182 (brs, 1H, C6-CH 2 ), 1.987 (brd, J = 6 Hz, 1H, C6-CH 2 ), 2.451 (t, 2H, C7-CH 2 ), 3.506 (o, 1H, C9-CH-), 2.433 (dd, J = 4.2, 2.4 Hz, 2H, C11-CH 2 ), 2.557 (dd, J = 12, 7.2 Hz, 2H, C12-CH 2 ), 7.10 (brs, 1H, C14-CH-), , 4.91 (brs, 2H, C15-CH 2 ), 4.595 (brs, 1H, C17-CH 2 ), 4.455 (brs, 1H, C17-CH 2 ), 1.599 (o, 3H, C18-CH 3 ), 4.207 (brs, 1H, C19-CH 2 ), 4.189 (brs, 1H, C19-CH 2 ), 0.71 (s, 3H, C20-CH 3 ), "o" denotes overlapping signals; 13 (Poonam et al, 2010) of the same compound, AB-2 was unambiguously identified as 14deoxyandrographolide ( Fig. 2).…”
Section: Bioassay Guided Isolationmentioning
confidence: 99%
“…Recently, other investigators studied the cytotoxic potential of andrographolide on M. microti [24] and M. bovis [25], and reported that it was non-cytotoxic at concentrations at which more than 96% inhibition was observed.…”
Section: Identification Of Compounds Frommentioning
confidence: 98%
“…It is widely used as an antidote against poisons of snakes and insect, and as an antimalarial agent (Dua et al, 1999). It is beneficial in general debility, asthma, bronchitis, filariasis and in hepatitis during clinical studies (Kulyal et al, 2010). It has a broad range of pharmacological effects (Roy et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Literature survey shows wide spectrum of pharmacological activities of kalmegh either in the form of powder, extracts or in its isolated compounds with minimum side effects (Niranjan et al, 2010). About 26 different formulations of this plant are mentioned in Ayurveda as a popular remedy for liver disorders, bowl complaints of children, colic pain, common cold and upper respiratory tract infections (Kulyal et al, 2010;Wen-Wan Chao and Lin, 2010). It is widely used as an antidote against poisons of snakes and insect, and as an antimalarial agent (Dua et al, 1999).…”
Section: Introductionmentioning
confidence: 99%